2016
DOI: 10.1039/c5cp07970e
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fe cations in ruthenium-complex multilayers fabricated by a layer-by-layer method

Abstract: Molecular multilayers were fabricated using a Ru complex containing Fe cations on an indium tin oxide surface to control the properties of the Ru-complex multilayers such as the multilayer orientation and the electron transport. The Ru-complex multilayer films containing Fe cations were thicker than those containing Zr cations, which have been used previously. The electron transport properties of the multilayers containing Fe cations were evaluated. Solid-state sandwich cell measurements showed that the Ru-com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
(78 reference statements)
0
5
0
Order By: Relevance
“…The kinetics were comparable at 456 and 380 nm, and decayed with a rate constant of 3.0 × 10 8 s –1 . Similar excited state quenching of ruthenium coordination complexes by Cu II , , Mn II , , and Fe II ions was observed previously and attributed to either energy (eq ) or electron transfer (eq ). …”
Section: Resultsmentioning
confidence: 90%
“…The kinetics were comparable at 456 and 380 nm, and decayed with a rate constant of 3.0 × 10 8 s –1 . Similar excited state quenching of ruthenium coordination complexes by Cu II , , Mn II , , and Fe II ions was observed previously and attributed to either energy (eq ) or electron transfer (eq ). …”
Section: Resultsmentioning
confidence: 90%
“… Although the metal ion loading process can be fast (<15 min), , MO 2 -B films were submerged in metal ion solution overnight to ensure complete coordination. For these films, the metal ion coordination is not surprising given that these ions were specifically selected because the metal ions and the starting salts are known to readily coordinate to CO 2 H and/or PO 3 H 2 groups as described in the metal–organic framework literature. …”
Section: Resultsmentioning
confidence: 99%
“…39 Incorporation of redox active linking ions like Fe 2+ increased the electron transport capabilities of the film via both hopping and tunneling mechanisms. 40 XPS, ellipsometry, and TOF-SIMS measurements indicated that multilayer growth was initially limited to 6−7 layers, which the authors attribute to the large tilt angle creating a domain boundary as depicted in Figure 6. 41 However, through variation in the film loading conditions, Haga and co-workers increased the monolayer loading and film uniformity, enabling the formation of at least 65 monolayers.…”
Section: Redox Active Ruthenium Polypyridyl Multilayersmentioning
confidence: 99%
“…Cyclic voltammograms of the films exhibited nonequivalent anodic and cathodic currents depending on the energetic/redox ordering of the species, indicating that multilayers can potentially serve as a rectifying interface . Incorporation of redox active linking ions like Fe 2+ increased the electron transport capabilities of the film via both hopping and tunneling mechanisms …”
Section: Metal Ion-linked Assemblies On Planar Surfacesmentioning
confidence: 99%